Genetic Characterization of Primary Mediastinal B-Cell Lymphoma: Pathogenesis and Patient Outcomes - Noerenberg, Daniel; Briest, Franziska; Hennch, Cornelius; Yoshida, Kenichi; Hablesreiter, Raphael; Takeuchi, Yasuhide; Ueno, Hiroo; Staiger, Annette M.; Ziepert, Marita; Asmar, Fazila; Locher, Benjamin N.; Toth, Erika; et al. (Journal of clinical oncology, 2024)
PURPOSEPrimary mediastinal large B-cell lymphoma (PMBCL) is a rare aggressive lymphoma predominantly affecting young female patients. Large-scale genomic investigations and genetic markers for risk stratification are lacking.PATIENTS AND METHODSTo elucidate the full spectrum of genomic alterations, samples from 340 patients with previously untreated PMBCL were investigated by whole-genome (n = 20), whole-exome (n = 78), and targeted (n = 308) sequencing. Statistically significant prognostic variables were identified using a multivariable Cox regression model and confirmed by L1/L2 regularized regressions.RESULTSWhole-genome sequencing revealed a commonly disrupted p53 pathway with nonredundant somatic structural variations (SVs) in TP53-related genes (TP63, TP73, and WWOX) and identified novel SVs facilitating immune evasion (DOCK8 and CD83). Integration of mutation and copy-number data expanded the repertoire of known PMBCL alterations (eg, ARID1A, P2RY8, and PLXNC1) with a previously unrecognized role for epigenetic/chromatin modifiers. Multivariable analysis identified six genetic lesions with significant prognostic impact. CD58 mutations (31%) showed the strongest association with worse PFS (hazard ratio [HR], 2.52 [95% CI, 1.50 to 4.21]; P < .001) and overall survival (HR, 2.33 [95% CI, 1.14 to 4.76]; P = .02). IPI high-risk patients with mutated CD58 demonstrated a particularly poor prognosis, with 5-year PFS and OS rates of 41% and 58%, respectively. The adverse prognostic significance of the CD58 mutation status was predominantly observed in patients treated with nonintensified regimens, indicating that dose intensification may, to some extent, mitigate the impact of this high-risk marker. By contrast, DUSP2-mutated patients (24%) displayed durable responses (PFS: HR, 0.2 [95% CI, 0.07 to 0.55]; P = .002) and prolonged OS (HR, 0.11 [95% CI, 0.01 to 0.78]; P = .028). Upon CHOP-like treatment, these patients had very favorable outcome, with 5-year PFS and OS rates of 93% and 98%, respectively.CONCLUSIONThis large-scale genomic characterization of PMBCL identified novel treatment targets and genetic lesions for refined risk stratification. DUSP2 and CD58 mutation analyses may guide treatment decisions between rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone and dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab.